Assessment of Long-Term Proppant Conductivity - Wang, Jun; Xiong, Youming; Jiao, Guoying; Lei, Dengsheng (Frontiers in Energy Research, 2022)
Long-term conductivity data is essential to predict the production performance of the fractured well. It is necessary to know its long-term conductivity when choosing Tianxiang ceramic to prop hydraulic fractures in Northwest China. Its long-term conductivity was evaluated using DL-2000 equipment. Testing time at each closure stress point is more than 7 h, though the procedure used is similar to the recommended practice for short-term proppant conductivity. This test also investigates how factors such as proppant concentration and proppant size affected long-term conductivity. The results show these factors have a significant effect on long-term conductivity. Conductivity increases as proppant concentration rises, contributing to the increase of proppant volume and fracture height. Large proppants provide higher conductivity because large proppants have higher pore space and higher proppant pack height. High experimental temperature increases proppant conductivity due to dissolution and migration of minor fines and impurities. Besides, due to compaction, conductivity declines with the increase of testing time. Therefore, short-term conductivity is higher than long-term conductivity, while conductivity drops as testing time lasts. The results imply that Tianxiang ceramic performs as well as other ceramic proppants. It can offer proppant conductivity required by stimulation and qualifies to stimulate oil and gas wells in China. The achievements of this experiment will benefit hydraulic fracturing stimulation.